2012
DOI: 10.1002/ptr.4686
|View full text |Cite
|
Sign up to set email alerts
|

Monoterpenes with Analgesic Activity—A Systematic Review

Abstract: There is still the need for efficacious therapies for pain. In the search for new therapeutic options, plants are a major source of novel biomolecules. Monoterpenes constitute 90% of essential oils, and there is a growing interest in understanding the mechanisms underlying their pharmacological activity. This systematic review reports what is so far known about the analgesic activity of monoterpenes and also provides an overview of their mechanisms of action. The search terms analgesia, anti-inflammatory, anae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
202
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 258 publications
(217 citation statements)
references
References 123 publications
2
202
0
2
Order By: Relevance
“…Moreover, the presence of diterpene and triterpene has also been confirmed ). Due to the consistent presence of flavonols and terpenes in AEC, it is possible to suggest that these compounds contributed to the analgesic effect, since several studies have described the analgesic and anti-inflammatory profiles of these compounds (Guimaraes et al 2013;S a et al 2013Souza et al 2014). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the presence of diterpene and triterpene has also been confirmed ). Due to the consistent presence of flavonols and terpenes in AEC, it is possible to suggest that these compounds contributed to the analgesic effect, since several studies have described the analgesic and anti-inflammatory profiles of these compounds (Guimaraes et al 2013;S a et al 2013Souza et al 2014). …”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the use of medicinal plants as an optional treatment has been increasing, especially in developing countries. Hence, chemical and pharmacological studies are essential for the usage to become safe and improve effectiveness (Guimaraes et al 2013(Guimaraes et al , 2014Quintans et al 2014). Chrysobalanus icaco L. (Chrysobalanaceae), popularly kwon as 'abajeru' or 'grageru', is a medicinal plant common in tropical areas.…”
Section: Research Articlementioning
confidence: 99%
See 1 more Smart Citation
“…In vitro studies have revealed that pulegone is a selective COX-2 inhibitor and probably acts through the inhibition of the production of inflammatory mediators from the cascade of cyclooxygenase (9). In addition, a study to evaluate the correlation between structure and anti-nociceptive activity demonstrated that pulegone showed an antinociceptive against the pain response induced by acetic acid (10). These properties of pulegone made it favorable for the authors to conduct a study to evaluate its wound healing potentials.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, it can include natural products (Bonjardim et al, 2011;Paixão et al, 2013). It can highlight the monoterpenos within the natural products, which are the main chemical constituents of the essential oils of plants with therapeutic properties (Edris, 2007;Guimarães et al, 2013;Silva et al, 2007). These molecules and their derivatives exhibit several types of pharmacological properties, such as anxiolytic (Silva et al, 2007), analgesic (Guimarães et al, 2010(Guimarães et al, , 2013Quintans-Júnior et al, 2011a, b), antiinflammatory (Guimarães et al, 2012) 2006c, 2007Passos et al, 2009) and anti-inflammatory and antibacterial activities (Botelho et al, 2009).…”
Section: Introductionmentioning
confidence: 99%